2020
DOI: 10.1186/s40575-020-00096-6
|View full text |Cite
|
Sign up to set email alerts
|

Breeding schemes for intervertebral disc disease in dachshunds: Is disc calcification score preferable to genotyping of the FGF4 retrogene insertion on CFA12?

Abstract: Background Approximately every fifth Dachshund is affected by disc herniation - a painful, hereditary condition which is typically preceded by disc calcification. Therefore, the selection of dogs suitable for breeding can be based on radiographic examination of calcification status. Recently, an insertion of an FGF4 retrogene on CFA12 has been identified and associated with the risk of developing disc herniation in chondrodystrophic breeds and a DNA test is now offered. In this study we investigate the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 18 publications
5
14
1
Order By: Relevance
“…The additive effect of the FGF4L2 retrogene on IVD calcification has now been demonstrated in several studies where interrogation of data from segregating populations has made analysis possible. 1,18 In addition to the current study, similar effects were shown across breeds presenting for surgically confirmed disc extrusions 1 and in Wire-haired Danish Dachshunds where genotype and calcification Table 1-Median (range) and coefficient of variation of geometric parameters of the third cervical vertebra in 21 dogs with 0 (n = 7), 1 (8), or 2 FGF4L2 retrogenes (7). screening scores were reported.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The additive effect of the FGF4L2 retrogene on IVD calcification has now been demonstrated in several studies where interrogation of data from segregating populations has made analysis possible. 1,18 In addition to the current study, similar effects were shown across breeds presenting for surgically confirmed disc extrusions 1 and in Wire-haired Danish Dachshunds where genotype and calcification Table 1-Median (range) and coefficient of variation of geometric parameters of the third cervical vertebra in 21 dogs with 0 (n = 7), 1 (8), or 2 FGF4L2 retrogenes (7). screening scores were reported.…”
Section: Discussionsupporting
confidence: 74%
“…It has been shown that the FGF4L2 retrogene is sufficient to cause chondrodystrophy and associated premature IVD degeneration; 5 however, only circumstantial evidence suggests that FGF4L2 retrogene dosage is associated with clinical disease severity. IVD calcification scores have been shown to be related to risk for "clinical" IVDD, [18][19][20][21][22] and the number of calcified IVD, as in the current study, is associated with genotype. 1,18 The effect of the FGF4L2 retrogene on IVD calcification appears to be definable in segregating populations; however, considerable variation in calcification is present even within the FGF4L2 homozygous populations of fixed and segregating breeds alike.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The increased application of genome and exome sequencing has facilitated a new era of understanding painful and progressive pathologies [3]. The genetic component to polygenic pathologies such as IVDD has been increasingly more characterized, with genome-wide association studies finding mutants, variants, and polymorphisms to genes that adversely influence the structure and function of the intervertebral disc (IVD) [4]. These genes may either gain or lose their function in supporting the IVD, leading to degenerative, apoptotic, and inflammatory signaling pathways that stimulate the pathogenesis of IVD degeneration [5].…”
Section: Introductionmentioning
confidence: 99%